Notebook and documents - Sturt, John Richard 1820-1886. (1788)
Sturt family register of births and deaths. Registered notice of death of John Richard Sturt. The last will and testament of J. R. Sturt. Account from Funeral Furnishers for coffin and hearse. Also includes two photographs of John Richard Stuart and two "In Memoriam" cards.
Manuscript reference: NLA MS 3138.
Keywords: Sturt family; Sturt, John Richard -- 1820-1886 -- Will